Physical Examination—Indicated Cerclage in Twin Pregnancy: A Randomized Controlled Trial. Issue 5 (May 2021) - Roman, Amanda; Zork, Noelia; Haeri, Sina; Schoen, Corina N.; Saccone, Gabriele; Colihan, Sarah; Zelig, Craig; Gimovsky, Alexis C.; Seligman, Neil S.; Zullo, Fulvio; Berghella, Vincenzo
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223:902.e1–902.e11) Twin pregnancies in the United States represent a small proportion of births each year, but they are associated with increased risks of preterm birth (PTB), low birthweight, and perinatal mortality. In the setting of cervical dilation in the second trimester, the risks for complications in a twin pregnancy are even higher.